Analisis Ekspor Kayu Manis Indonesia ke Amerika Serikat - Yulmi Nur Asrini; Siti Hodijah; Nurhayani Nurhayani (Jurnal Ekonomi Aktual, 2021)
This study aims to analyze the development of Indonesia’s export volume of cinnamon to the United States, cinnamon export prices, exchange rates, and domestic cinnamon production. It also aims to analyze the influence of cinnamon export prices, exchange rates, and domestic cinnamon production on Indonesia’s cinnamon exports to the United States from 2000-2017. The data used were obtained from the official website of Statistics Indonesia, United Nations Commodity Trade (COMTRADE), and the Plantation Office. The data analysis method used in this study is descriptive and quantitative methods with multiple linear regression analysis. Based on the multiple linear regression analysis results, it was concluded that simultaneously the prices of exported cinnamon, the exchange rate, and the domestic cinnamon production had a significant effect on the export of Indonesian cinnamon to the United States. Partially, the exchange rate and the production of domestic cinnamon had a significant effect. Still, the price of exported cinnamon did not significantly influence the export of Indonesian cinnamon to the United States.